Viewpoint: The Discomfort of Interdisciplinarity- New ways of looking at familiar things - Tania Katzschner (Environmental Association of Southern Africa, 2010)
As the requirements of sustainable development become less and less questionable and as we discover that many of our issues that are usually considered separate are actually interwoven in all sorts of mutually dependent ways, we are being called upon to consider how to more effectively deal with interlocking issues. This paper introduces some of the issues and challenges around working across disciplines and attempts to draw attention to perceptions, challenges, misunderstandings, contradictions and pitfalls of interdisciplinary initiatives. Overall the paper aims to offer new insights and perspectives and to contribute towards developing more interest, curiosity and competence in this challenging topic. The focus of discussion and the research questions raised relate to the university environment.